RATIONALISM IN PRASTARI’S MISTERI DELMAN MERAH JAMBU - Mateus Rudi Supsiadji; Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, 2017)
Abstract. This article explores rationalismin Prastari’s Misteri Delman Merah Jambu. Rationalism covers the idea that human beings can arrive at truth by using reason, rather than relying on past authority, religious institutions, or on intuition. In Prastari’s Misteri Delman Merah Jambu, rationalism is presented through the character Alva. In his reaction towards the prohibition for children under 15 to stay at home before 7 at the evening, Alva tries to discover the reason behind this prohibition. He does not believe in what other children believe that there is a supernatural power represented by Delman Merah Jambu (pink horse cart) rode by a beautiful lady in white clothes. The writer applied the qualitative confirmatory method in conducting the research. Key words: rationalism, supernatural power, reason